2021
DOI: 10.1111/jvh.13625
|View full text |Cite
|
Sign up to set email alerts
|

Serum α‐fetoprotein level at treatment completion is a useful predictor of hepatocellular carcinoma occurrence more than one year after hepatitis C virus eradication by direct‐acting antiviral treatment

Abstract: Direct-acting antivirals (DAAs) have recently been developed to treat hepatitis C virus (HCV) infection, and interferon-free DAA treatment has improved liver function of HCV patients. The risk of hepatocellular carcinoma (HCC) occurrence following HCV eradication has been previously reported, but HCC may have been missed following imaging diagnosis before DAA administration in previous studies. Therefore, the present study aimed to identify definite predictors of HCC occurrence ≥1 year after DAA treatment. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…Serum AFP concentration has also been found to predict HCC development[ 10 , 13 ]. Higher AFP concentration is a major biomarker for HCC occurrence after SVR[ 28 , 29 ], as well as being associated with liver inflammation, making AFP concentration at the end of treatment very important[ 30 ]. AFP concentrations before and after DAA treatment should therefore be measured to estimate the risk of HCC recurrence/occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Serum AFP concentration has also been found to predict HCC development[ 10 , 13 ]. Higher AFP concentration is a major biomarker for HCC occurrence after SVR[ 28 , 29 ], as well as being associated with liver inflammation, making AFP concentration at the end of treatment very important[ 30 ]. AFP concentrations before and after DAA treatment should therefore be measured to estimate the risk of HCC recurrence/occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has focused on analysing the roles and mechanisms of zinc (Zn) in the pathogenesis of hepatitis C virus (HCV) and have reported that the oxidative stress causes a disruption in zinc (Zn) homeostasis, in particular, in the signalling molecule and secondary messenger through the redox process, resulting in HCV-mediated mitochondrial dysfunction [80]. It is worth mentioning that, upon viral eradication using interferon (IFN)-based regimens or direct-acting anti-viral (DAA) therapy, zinc (Zn) serum levels were shown to rise significantly, which reflects the hepatic inflammation's resolution as well as an improvement in the gut absorption [33].…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…Zinc (Zn) serum levels were shown to rise significantly upon viral eradication using interferon (IFN)-based regimens or direct-acting anti-viral (DAA) therapy [33].…”
mentioning
confidence: 99%
“…Although HCV eradication with DAAs reduces the incidence of HCC, the unexpected early occurrence of HCC after sustained virological response (SVR) has been reported. 9 , 10 , 11 , 12 The increasing number of patients achieving HCV clearance with DAAs and the continued risk of hepatocarcinogenesis even after SVR requires the follow‐up of these patients. Loss to follow‐up (LTFU), which refers to patients who start care but voluntarily stop it, is a problem for those with chronic disease.…”
Section: Introductionmentioning
confidence: 99%